Development of Sparkol Vidoescribe Learning Media to Increase The Students Learning Motivation in Fiqh Subject - Siti Fatimah; Maemunah Sa’diyah (Lembaga Pengembangan Pendidikan dan Pembelajaran, Universitas Negeri Malang in Collaboration with Asosiasi Pendidik dan Pengembang Pendidikan Indonesia (APPI), 2020)
This research aims to define the expediency of Sparkol learning media Videoscribe and see the learning media Sparkol Videoscribe affects the student motivation in class X. This research uses Research and Development. The research data shows that the media expert is equal to 91.18% while subject experts were 80.556%. At the testing stage, individual trials show the number 86% while for testing to small group pointed at 98%. The final result of the test, the validation test show marks the sig 0.00 <0.05 with differences in results of class control at 74.31% and 82.06% at the experimental class. In conclusion, the development learning media Sparkol Videoscribe as a Fiqh teaching material is worthy of use to increase the motivation in student learning.